Rapid detection of 2, 2′, 4, 4′‐tetrabromodiphenyl ether (BDE‐47) using a portable Au‐colloid SERS sensor. (15th July 2014) - Sun, Zhenli; Du, Jingjing; Yan, Li; Jing, Chuanyong
<x xml:space="preserve">Abstract</x> In situ rapid detection and identification of polybrominated diphenyl ethers, a group of well‐known persistent organic pollutants, present a great challenge. To develop a portable and sensitive surface‐enhanced Raman scattering (SERS) sensor for rapid 2, 2′, 4, 4′‐tetrabromodiphenyl ether (BDE‐47) detection, we adopted the most commonly used Au nanoparticles, which are effective in the analysis of hydrophobic BDE‐47 with a simple optimization in citrate content and sampling technique. Qualitative and quantitative determination of BDE‐47 was achieved using a portable Raman spectrometer. The SERS response exhibited a linear dependence on the BDE‐47 concentration up to 1000 nM with a detection limit of 75 nM. The density function theory‐calculated Raman spectra agreed well with the experimental observations, and the results justified the existence of electromagnetic enhancement and charge transfer mechanism. This in situ SERS platform allows easy and reliable detection of hydrophobic molecules such as BDE‐47 in complex matrices. Copyright © 2014 John Wiley & Sons, Ltd.